Efisiensi Teknis, Ekonomi, dan Alokatif Usahatani Jagung di Kabupaten Lampung Selatan - Sri Puji Lestari; Dyah Aring Hepiana Lestari; Zainal Abidin; Fembriarti Erry Prasmatiwi (Politeknik Negeri Lampung., 2023)
South Lampung Regency is the center of corn production in Lampung Province. However, the low productivity of corn due to the suboptimal allocation of production factors has affected the efficiency of corn farming production. This research aims to analyze the level of technical, allocative, and economical efficiency corn farming in South Lampung Regency. Two subdistricts in South Lampung Regency—Penengahan and Ketapang—that are major corn production hubs were used for data collection. The data collected in this study are primary and secondary. Primary data was obtained using a survey method, namely by directly interviewing corn farmers using a list of questions (a questionnaire) that has been provided. Secondary data were obtained from institutions or agencies related to this research. A simple random sampling method was used to choose up to 71 maize producers for the sample size. The Stochastic Frontier Cobb-Douglas production function is used in data analysis and is processed by the Frontier 4.1 application. The results show that corn farming was technically efficient but not allocatively or economically efficient.. The use of inputs appropriately and efficiently will reduce the use of excessive inputs, which can then be allocated to the purchase of other inputs that are less used, with the aim of achieving allocative and economic efficiency.